Best M-term trigonometric approximations of the classes of periodic functions of many variables in the space Lq - Konohrai, A. F.; Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We obtain order estimates for the best M-term trigonometric approximations of classes B Ωp,θ of periodic multivariable functions in the space Lq for some values of the parameters p and q.